Entertainment and Agriculture: An Examination of the Impact of Entertainment Media on Perceptions of Agriculture - Lisa K. Lundy; Amanda M. Ruth; Travis D. Park (Journal of Applied Communications, 2007)
This study was conducted as a follow-up to Ruth, Park, and Lundy's 2005 study, which found that the portrayal of agriculture in reality television programming reinforced traditional stereotypes of agriculture and corresponding schemas. Qualitative focus groups were conducted in July 2005 with undergraduate students at a large southern university. Participants responded to questions about their perceptions of agriculture and then reacted to a short clip from the 2004 film Napoleon Dynamite that featured agriculture. This study substantiated Ruth et al.'s findings that entertainment media have potential short -term and long-term effects on individuals' perceptions of agriculture. While portrayals of agriculture in entertainment media may not actually create negative perceptions of agriculture, they may serve as significant reinforcement for existing negative stereotypes and perceptions. Since many young adults hold uninformed stereotypes about agriculture that are reinforced by entertainment media, agricultural communicators are challenged to communicate the significance of agriculture to this audience in a format they perceive as relevant.